PENERAPAN STRATEGI ACTIVE KNOWLEDGE SHARING DALAM MENINGKATKAN HASIL BELAJAR PADA MATA PELAJARAN IPS SISWA KELAS IV SD NEGERI 3 SULAHAN - Mawarensa, Ismi Arum; Numertayasa, I Wayan; Astuti, Ni Putu Eni (Jurnal Pendidikan Dasar Rare Pustaka, 2024)
Abstract This classroom action research was conducted to improve social studies learning outcomes for fourth grade students at Public Elementary School 3 Sulahan by using an active knowledge-sharing strategy. The factors that cause low learning outcomes are the lack of student participation in ongoing teaching and learning activities, but the use of appropriate methods and strategies during the learning process can be one of the factors that influence student learning activities. Grade IV students at Public Elementary School 3 Sulahan, totaling 23 students, were the subjects of this study. Meanwhile, the object of this research is active knowledge-sharing learning strategies and learning outcomes of social studies class IV Public Elementary School 3 Sulahan. The research data was collected using a method consisting of observation, testing, and documentation, which was then analyzed using a shooting technique with a 70% shot. The results of the pre-test showed an average score of 60.39, and the proportion of completeness was 26.09%. The results of the first cycle showed an average of 69.57 with 52.17% completeness. The results of cycle II get an average of 85.61 with 86.96% completeness. The findings from the analysis of this study mean that learning using an active knowledge-sharing strategy has increased the social studies learning outcomes of fourth grade students at Public Elementary School 3 Sulahan. Keywords: Active knowledge sharing strategies, Learning outcomes